Analisis Faktor–Faktor yang Mempengaruhi Impor Kapas di Indonesia - Nevira Refli Yuniandini; Niniek Imaningsih; Riko Setya Wijaya (Jurnal Syntax Admiration, 2024)
The purpose of this study is to determine and examine if cotton imports into Indonesia are influenced by cotton prices, cotton consumption, cotton production and exchange rate.. This study falls under the category of quantitative research. Data on cotton prices, cotton consumption, cotton production, exchange rate, and cotton imports make up this study population. The study sample consists of yearly data from Indonesia organized into timeseries that are consecutive and span the years 2003 through 2020. The secondary data documentation approach is the data gathering strategy used in this study. The analysis technique used is multiple linear regression analysis which meets the BLUE (Best Linear Unbiased Estimate) assumption. Based on the statistical t test results, the variable Cotton Prices (X1) 3,299 > ttable 2,160, Cotton Consumption (X2) = 6,398 > ttable 2,160, Cotton Production (X3) = 4,324 > ttable 2,160, and that the Exchange Rate (X4) = 3,128 > ttable 2,160 has an effect on Cotton Imports (Y) in Indonesia. The result of statistical testing indicates that H0 is rejected when Fcount > Ftable. The research found that although the four variables Cotton Prices (X1), Cotton Consumption (X2), Cotton Production (X3), and Exchange Rates (X4) had a simultaneous and limited influence on Imports of Cotton (Y), the Cotton Prices (X1) variable had the most impact.